Management of acute perioperative myocardial infarction: a case report of concomitant acute myocardial infarction and tumor bleeding in the transverse colon - Li, Yu-Feng (Clin Interv Aging, 2016)
Acute myocardial infarction complicated by bleeding colon tumor is problematic with regard to management, and appropriate balance of antiplatelet or anticoagulation therapy and hemostasis or surgery is crucial for effective treatment. Here, we present a case of concomitant acute myocardial infarction and bleeding tumor in the transverse colon, and share our experience of successfully balancing anticoagulation therapy and hemostasis.